1990
DOI: 10.1002/elps.1150110908
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical dynamics of isoelectric focusing: IV. Cathodic, anodic and symmetrical drifts of the pH gradient

Abstract: The production of anodic, cathodic and symmetrical drifts of a pH 3.5-10 gradient formed by isoelectric focusing in polyacrylamide gels is demonstrated experimentally by manipulation of the electrolyte concentrations. Experimental behavior is reproduced by computer simulation of a model mixture of 15 hypothetical carrier ampholytes whose pIs span the pH range 3-10. The mechanism which produces the drifts is elucidated and approaches to minimize such drifts are discussed. The data suggest why most experimentall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(90 citation statements)
references
References 7 publications
6
84
0
Order By: Relevance
“…The nature of catholyte and anolyte in CIEF is of importance in order to control anodic and/or cathodic drift, which was described for slab gel IEF as a pH instability that causes a progressive loss of the acid and basic end of the pH gradient, respectively [16]. This drift could be a difficulty in AGP analysis, because this protein being very acidic and focused in the far end of the capillary, ampholytes loss caused by anodic drift can drag AGP sample down the reservoir.…”
Section: Selection Of Catholytementioning
confidence: 99%
“…The nature of catholyte and anolyte in CIEF is of importance in order to control anodic and/or cathodic drift, which was described for slab gel IEF as a pH instability that causes a progressive loss of the acid and basic end of the pH gradient, respectively [16]. This drift could be a difficulty in AGP analysis, because this protein being very acidic and focused in the far end of the capillary, ampholytes loss caused by anodic drift can drag AGP sample down the reservoir.…”
Section: Selection Of Catholytementioning
confidence: 99%
“…35 Dynamic computer simulation of electrophoresis has already demonstrated considerable value as a research tool. Since the 1980s, numerical simulations have been performed to better understand and describe IEF [36][37][38][39][40] and have shown a qualitative agreement between predictions and experimental results. Recent advances in computer simulation have led to the development of a simulator that can handle up to 150 components and voltages typically used in experiments.…”
Section: Introductionmentioning
confidence: 96%
“…In work exploring the impacts and uses of moving boundaries in IEF, simulations performed with GENTRANS revealed that the gradual decomposition of the pH gradient at the buffer gradient interfaces [53,158,159] (for an example see Fig. 15), electrophoretic mobilization after focusing [132] and IEF with concurrent electrophoretic mobilization [160] are ITP based processes (see Section 4.3).…”
Section: Aspects Of Itp and Mbementioning
confidence: 99%
“…Early work was performed with a current density typically much lower than that employed in the laboratory and with the number of components limited to 15, which provided qualitative information about the system, but could not be used in any quantitative capacity. Nevertheless, these simulations provided new insights into the separation, stabilizing and destabilizing processes of IEF of simple ampholytes and proteins in closed columns without electrolytes and in configurations with acid and base as anolyte and catholyte, respectively [158,163,[168][169][170]. Simulation was also employed to study the formation of stable pH gradients with weak monovalent buffers for IEF in free solution [146], for the investigation of the stability of stepwise pH gradients used in continuous flow electrophoresis [171], to visualize pH gradient formation together with protein focusing for IEF field flow fractionation [172,173] and to visualize continuous trapping of an ampholyte [174] and separation of proteins [175] in carrier free IEF.…”
Section: Fundamentals Of Iefmentioning
confidence: 99%
See 1 more Smart Citation